Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1200/jco.2019.37.7_suppl.575
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with metastatic clear cell renal cell carcinoma treated with second-line VEGFR-TKI after first-line immune checkpoint inhibitors.

Abstract: 575 Background: Immune checkpoint inhibitors (ICI) are being increasingly utilized in front-line (1L) setting of metastatic clear-cell renal cell carcinoma (mccRCC). Limited data exist on responses and survival on second-line (2L) VEGFR-TKI therapy after 1L ICI therapy. Methods: This is a retrospective study of mccRCC patients treated with 2L VEGFR-TKI after progressive disease (PD) with 1L ICI. Patients were treated at MD Anderson Cancer Center or Memorial Sloan Kettering Cancer Center between December 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…8,22 The METEOR trial and Checkmate 025, investigating cabozantinib and nivolumab after TKI failure, respectively, both reported an ORR of 21%, 23,24 while a pooled analysis of patients treated with second-line TKI monotherapy after IO at MDACC and Memorial Sloan Kettering Cancer Center revealed an ORR of 41.2%. 25 In our heavily pretreated mRCC cohort, combination TKI-IO achieved comparable, if not superior, response rates in reference to these monotherapy strategies. As further support for salvage TKI-IO use, one exceptional responder underwent consolidative cytoreductive nephrectomy following second-line TKI-IO exposure.…”
Section: Percent Of Cohort (%)mentioning
confidence: 74%
See 1 more Smart Citation
“…8,22 The METEOR trial and Checkmate 025, investigating cabozantinib and nivolumab after TKI failure, respectively, both reported an ORR of 21%, 23,24 while a pooled analysis of patients treated with second-line TKI monotherapy after IO at MDACC and Memorial Sloan Kettering Cancer Center revealed an ORR of 41.2%. 25 In our heavily pretreated mRCC cohort, combination TKI-IO achieved comparable, if not superior, response rates in reference to these monotherapy strategies. As further support for salvage TKI-IO use, one exceptional responder underwent consolidative cytoreductive nephrectomy following second-line TKI-IO exposure.…”
Section: Percent Of Cohort (%)mentioning
confidence: 74%
“…Despite 77.1% of patients in receiving at least two lines of prior systemic therapy, our observed ORR of 51% was similar to that of prospective first‐line TKI–IO trials 1,2 as well as previously published phase 1 data for nivolumab–pazopanib and nivolumab–cabozantinib in the salvage setting—45% and 36% respectively 8,22 . The METEOR trial and Checkmate 025, investigating cabozantinib and nivolumab after TKI failure, respectively, both reported an ORR of 21%, 23,24 while a pooled analysis of patients treated with second‐line TKI monotherapy after IO at MDACC and Memorial Sloan Kettering Cancer Center revealed an ORR of 41.2% 25 . In our heavily pretreated mRCC cohort, combination TKI–IO achieved comparable, if not superior, response rates in reference to these monotherapy strategies.…”
Section: Discussionmentioning
confidence: 95%
“…Limited trial data exist on the efficacy of VEGFR-TKIs or cabozantinib after progression on ICIs. In three real-world studies, second-line VEGFR-TKIs, including cabozantinib, had similar or improved efficacy after disease progression on ICIs, compared with the post-VEGFR-TKI setting [18][19][20]. Cabozantinib is a multitarget TKI that inhibits VEGFR1-3, MET, AXL, RET, ROS1, TYRO3, MER, KIT, and FLT3 and is approved in the first-line and subsequent-line settings for mRCC based on results from the CABOSUN and METEOR trials, respectively [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a durable response to ICI has previously been reported [6], and in our case, the combination of pazopanib and the prolonged effect of nivolumab may have cause TLS, similar to TKI/ICI combination therapy. Previous reports on second-line TKI after ICI are summarized in Table 2 [14,15]. Each treatment has a certain level of therapeutic effect and AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment has a certain level of therapeutic effect and AEs. Shah et al [15] reported that 8 of 19 (42%) patients treated with pazopanib after ICI discontinued treatment due to its toxicity, and the most frequent reason (5 of 8, 63%) was transaminitis. The discontinuation rate of pazopanib was higher than that of other TKIs (13% for axitinib, 17% for sunitinib, 0% for cabozantinib).…”
Section: Discussionmentioning
confidence: 99%